Isolation and identification of Tete virus group (Peribunyaviridae: Orthobunyavirus) from Culicoides biting midges collected in Lichuan County, China - Yin, Qikai; Cheng, Rui; Xu, Xiuyan; Xu, Ziqian; Wang, Jing; Fu, Shihong; Xu, Hongbin; Zhang, Shaozai; He, Ying; Li, Fan; Xu, Songtao; Lu, Xiaoqing; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
In July 2018, a virus (JXLC1806-2) was isolated from Culicoides biting midges collected in Lichuan County, Jiangxi Province, China. The virus isolate showed significant cytopathic effects within 48 hours after inoculation with mammalian cells (BHK-21). JXLC1806-2 virus could form plaques in BHK-21 cells, and the virus titer was 1×105.6 pfu/mL. After inoculation with the virus, suckling mice developed disease and died. The nucleotide and amino sequence analysis showed that the JXLC1806-2 virus genome was composed of S, M and L segments. Phylogenetic analysis showed that the S, M and L genes of JXLC1806-2 virus belonged to the Tete serogroup, Orthobunyavirus, but formed an independent evolutionary branch from the other members of the Tete serogroup. The results showed that the JXLC1806-2 virus, which was named as Lichuan virus, is a new member of Tete serogroup, and this is the first time that a Tete serogroup virus has been isolated in China.